New technology for biochar production from oil palm empty fruit bunch - Rozhan, Alya Naili; Hamzah, Mohd. Salleh; Hadi , Purwanto (Asian Research Publishing Network, 2016)
This paper presents a process to utilize oil palm empty fruit bunch (EFB) by thermochemical conversion to produce carbon-infiltrated biochar, which can be used as an efficient alternative energy source. An integrated process of pyrolysis and decomposition of pyrolysis vapor was employed by chemical vapor infiltration (CVI) process. For preparation, raw EFB was made into highly porous biochar by slow pyrolysis process at 500-800°C to provide active sites for decomposition of pyrolysis vapor. In the general fast pyrolysis process of EFB, the main pyrolysis vapor product will undergo a secondary decomposition to produce secondary char and gases. In this study, this secondary decomposition is of interest. Fast pyrolysis of EFB was carried out at 400, 450 and 500°C to produce pyrolysis vapor to be infiltrated within the pores of biochar substrate and decomposed on its active sites. Secondary decomposition of pyrolysis vapor produced secondary char, where solid carbon was deposited within the porous biochar substrate, increasing the total carbon content of the resultant carbon-infiltrated biochar. This process was developed to produce a value-added EFB-derived biochar. One special application of this product is in steel industry, mainly in their sintering plants; as an efficient alternative energy source to partially substitute coke breeze